Enabling robust automotive electronic components in advanced CMOS nodes. (September 2017) - Huard, V.; Mhira, S.; Cacho, F.; Bravaix, A.
Abstract: In this work, we have demonstrated that many elements are needed on top of conventional foundry reliability knowledge to enable robust automotive products in compliance with all restrictive norms. For intrinsic reliability, both reliability models (a design compatible WLR description), and dynamic aging compensation schemes are required. For extrinsic failures, screening procedures require well documented usage and are shown in use for volume production to bring the failure rate level down below 1 ppm automotive target. Altogether, the global approach developed in STMicroelectronics enable robust automotive products based on controlled and validated procedures. Highlights: Demonstration of reliability methodology developed for manufacturing chain for high performance CMOS circuit conception. Conception of FDSOI circuits based on adaptive controlled loops with in-situ monitors for performance and high reliability. Static and Dynamic loops enables voltage adaptation as a function of activity and workloads with software management. Power savings in average (25%) validated on large sampling and formal validation at system level for automotive application.